Effect of internal control systems on financial performance of SME's. - NAMA HERMAN TENYWA (Uganda Christian University, 2024)
ABSTRACT The purpose of the study was to assess the effect of internal control systems on financial performance of SME’s in Buikwe District a case study of Senasa Distributors. The study was guided by three core objectives; firstly, to assess the effect of control environment on the financial performance of SME’s in the study context; secondly, to assess the effect of control activities on the financial performance of SME’s in the study context. And lastly, to assess the relationship between risk assessment and its effect on the financial performance of SMEs in the study context. Employing a case study design and adopting a purely quantitative methodology, data was collected from 66 respondents through structured questionnaires. The collected data was analysed using descriptive statistics. The study established a noteworthy discovery, based on increased responsibility, transparency and operational efficiency, the findings showed that a robust internal control environment considerably boosts financial performance. Control activities for example regular audits, segregation of duties and authority limits were found to lower on the high rates of fraud and errors which improves on the financial performance of businesses. The identification and mitigation of potential financial risks which guarantee the stability and growth of the business have also been demonstrated to be greatly aided by risk assessment. The study concludes that a strong internal control framework is necessary for SME’s to maintain their financial viability according to this study’s findings.